Credit Risk Management and Financial Performance of Commercial Banks in the UK - Zhou, Hui (2022)
This paper examines the relationship between credit risk management and financial performance of UK commercial banks. The non-performing loan ratio is used as an indicator of credit risk and the return on total assets is used as a measure of financial performance. The hypothesis discusses the impact of non-performing loan ratio and capital adequacy ratio on the financial performance of commercial banks and the mediator effect of asset adequacy ratio respectively. The sample is selected from 54 commercial banks in the UK, the unbalanced panel data is selected from 2005 to 2021, and the fixed effects regression model is constructed for the analysis. The results are that non-performing loan ratio has a significant negative effect on financial performance. Capital adequacy ratio has a significant positive effect on financial performance. What’s more, capital adequacy ratio is a suppressing effect, not a mediator effect in how the non-performing loan ratio affects financial performance.